AN INVESTIGATION OF THE IMPACT OF SOCIAL MEDIA ON BUSINESS VALUE AND FINANCIAL PERFORMANCE OF ORGANIC SKIN CARE BRANDS IN THAILAND - Napasorn Boonpreda; Ximing Ruan (Bina Nusantara University, 2020)
The adoption of social media in promoting cosmetic brands had changed the traditional approach to creating value for consumers, which subsequently improve the firms’ financial performance. With the organic skincare brands, the research empirically examined to what extent and aspects the business value is shaped by social media promotions. The research findings from the quantitative analysis suggest that the business value could be created through curation, collaboration, and creation in social media marketing.